2006
DOI: 10.5408/1089-9995-54.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Using Conceptests to Assess and Improve Student Conceptual Understanding in Introductory Geoscience Courses

Abstract: Conceptests are higher-order multiple-choice questions that focus on one key concept of an instructor's major learning goals for a lesson. When coupled with student interaction through peer instruction, conceptests represent a rapid method of formative assessment of student understanding, require minimal changes to the instructional environment and introduce many of the recognized principles of effective teaching that enhance student learning. In this study, instructors from several different institutions deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 29 publications
0
41
0
1
Order By: Relevance
“…Similarly, the Geoscience Concept Inventory (Libarkin and Anderson, 2006) represents a robust and highly successful instrument that addresses a broad variety of key geoscience concepts. Other geoscience concept test and questionnaire studies have taken a similarly broad approach (e.g., McConnell et al, 2006;Cervato et al, 2007), while some have focused specifically on a concept of particular concern, such as geologic time (Parham et al, 2005;Libarkin et al, 2007). In academic vernacular, these approaches could be distinguished as "conceptually extensive" and "conceptually intensive", respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Geoscience Concept Inventory (Libarkin and Anderson, 2006) represents a robust and highly successful instrument that addresses a broad variety of key geoscience concepts. Other geoscience concept test and questionnaire studies have taken a similarly broad approach (e.g., McConnell et al, 2006;Cervato et al, 2007), while some have focused specifically on a concept of particular concern, such as geologic time (Parham et al, 2005;Libarkin et al, 2007). In academic vernacular, these approaches could be distinguished as "conceptually extensive" and "conceptually intensive", respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Originally called ConcepTests by Mazur (1997), we choose to follow Piepmeier (1998), Gray (2009) and Mollborn and Hoekstra (2010) who used the term conceptest questions to refer to this type of question. Conceptest questions are available for a wide range of scientific and non-scientific disciplines wide range of disciplines including geoscience (Greer and Heany 2004;McConnell et al 2006), chemistry (Butcher et al 2003), math (Schlatter 2002), physics (Beatty et al 2006), Biology (Brewer 2004), nursing (Debourgh 2007), packaging (Auras and Bix 2007), and economics (Maier and Simkins 2008).…”
Section: Research On Conceptest Questionsmentioning
confidence: 99%
“…During the same time period, wide acceptance of personal response systems (colloquially known as 'clickers') in undergraduate science courses has transformed lecture courses by providing a means of utilizing an active-learning pedagogy in an otherwise passive learning environment. Numerous studies demonstrate effective ways of using personal response systems in a variety of disciplines (Beatty and Gerace 2009;Crouch and Mazur 2001;McConnell et al 2006) but very few studies have assessed whether student responses to the associated conceptually-based questions may be influenced by factors other than question content or student conceptual knowledge (King and Joshi 2008;Steer et al 2009). Given that personal response systems use a multimedia format, it is possible that student responses are influenced by design principles related to developing a good multimedia presentation.…”
Section: Introductionmentioning
confidence: 98%
“…Other elements of new education paradigm including metacognition, conceptual learning and social/peer and active learning approaches are also considered in our work. Several instructional approaches currently leverage one of these factors, however, peer instruction (Brill and Hodges 2010;Mazur 1997;Mazur and Watkins 2010) integrates the various elements by factoring peer/social learning (Michinov, Morice, and Ferrières 2015), student response (Donovan 2008), dialogue/group discussion (Smith et al 2009) or learning by teaching and metacognition/conceptual learning (Mcconnell et al 2006) in a single approach. The effectiveness of the learning-by-teaching approach has been highlighted in studies (Biswas et al 2005) and shown to yield even better results when combined with conceptual learning to promote metacognition.…”
Section: Pedagogy and Instructional Systemmentioning
confidence: 99%